Negotiating access for research on post-deportation - Schultz, Susanne U. (Research methods in deportation, 2024)
This chapter provides insights into negotiating access to research how deportees cope with having been deported and their situation back ‘home’. Based on qualitative fieldwork completed over eight months (2014-2016) in southern Mali, with institutional actors but mainly with deportees, covering their social surroundings in the capital and rural areas, it details the initial steps in an ethnography of conditions and situations post-deportation and includes elements of participatory and action research. The chapter centres on constituting the field in a context where (post-)deportees seem to be everywhere, a consequence of the extensive, diverse, long-lasting effects of deportations in Mali. As there is no ‘beyond positionality’, a critical reflection on my findings takes a prominent place, including an examination of specific power discrepancies, sometimes impossible to bridge. My research collaboration with a Malian anthropologist, which brought special benefits to doing research with deportees, particularly needs to be prominently featured.